The herpes simplex virus-1 transactivator infected cell protein-4 drives VEGF-A dependent neovascularization. - Todd Wuest; Min Zheng; Stacey Efstathiou; William P Halford; Daniel J J Carr (PLoS Pathogens)
Herpes simplex virus-1 (HSV-1) causes lifelong infection affecting between 50 and 90% of the global population. In addition to causing dermal lesions, HSV-1 is a leading cause of blindness resulting from recurrent corneal infection. Corneal disease is characterized by loss of corneal immunologic privilege and extensive neovascularization driven by vascular endothelial growth factor-A (VEGF-A). In the current study, we identify HSV-1 infected cells as the dominant source of VEGF-A during acute infection, and VEGF-A transcription did not require TLR signaling or MAP kinase activation. Rather than being an innate response to the pathogen, VEGF-A transcription was directly activated by the HSV-1 encoded immediate early transcription factor, ICP4. ICP4 bound the proximal human VEGF-A promoter and was sufficient to promote transcription. Transcriptional activation also required cis GC-box elements common to the VEGF-A promoter and HSV-1 early genes. Our results suggest that the neovascularization characteristic of ocular HSV-1 disease is a direct result of HSV-1's major transcriptional regulator, ICP4, and similarities between the VEGF-A promoter and those of HSV-1 early genes.